Environmental impacts of a highly congested section of the Pan-American highway in Peru using life cycle assessment - Verán-Leigh, D.; Larrea-Gallegos, G.; Vázquez-Rowe, I. (Springer Verlag, 2019)
Road construction and transportation generate significant environmental impacts. Hence, it is increasingly important to understand the environmental burdens produced throughout the different stages of road development: construction, maintenance, traffic, and end-of-life. In this study, life cycle assessment (LCA) was used as an environmental management methodology to determine the impacts associated with a 22.4 km stretch of the South Pan-American (PS) highway in the province of Lima, Peru, one of the main access routes for traffic and goods entering Lima, located in a hyper-arid area parallel to the Pacific Ocean.
Keywords: Highway; Industrial ecology; Infrastructure; LCA; Peru; Road construction; https://purl.org/pe-repo/ocde/ford#2.01.04